2017
DOI: 10.1007/s10098-017-1436-8
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the drivers, barriers, and incentives for environmental management systems in the Malaysian food and beverage industry

Abstract: Food production and consumption is one of the major causes of global environmental degradation. One way to address environmental impacts in the food and beverage (F&B) sector is via the adoption of environmental management systems (EMS). To date, EMS research has focused predominantly on countries and sectors based in the Global North despite growing recognition of the global extent of environmental impacts from food production and consumption. In order to widen our knowledge of this topic in an underresearche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 40 publications
1
49
0
2
Order By: Relevance
“…An effort to comply with governmental regulations will most likely become companies' motivation to be EMS‐certified, as research suggests that companies in developing countries and SMEs tend to be reactive rather than proactive (Brammer et al, ; Walker, Di Sisto, & McBain, ). Firms in emerging countries are also subject to weaker pressures from the demand side, where most local customers do not have a preference for buying green products (Salim, Padfield, Lee, et al, ). The high certification cost of ISO 14001 is also reported as a critical problem for companies operating in developing countries (Massoud et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…An effort to comply with governmental regulations will most likely become companies' motivation to be EMS‐certified, as research suggests that companies in developing countries and SMEs tend to be reactive rather than proactive (Brammer et al, ; Walker, Di Sisto, & McBain, ). Firms in emerging countries are also subject to weaker pressures from the demand side, where most local customers do not have a preference for buying green products (Salim, Padfield, Lee, et al, ). The high certification cost of ISO 14001 is also reported as a critical problem for companies operating in developing countries (Massoud et al, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Environmental standards have increasingly governed the global food market and trade, especially due to the increased consumer demand for green products in the Global North (Neumayer & Perkins, 2004;Padfield et al, 2016). EMS standards engender exclusion to those countries that only have a few EMS-certified companies (Morris & Dunne, 2004;Salim, Padfield, Lee, et al, 2018), because companies and consumers in the Global North tend to source green materials or products, whereas companies in the Global South are less able to meet the environmental standard (Arimura, Darnall, & Katayama, 2011). The most widely recognized standard for an EMS is the ISO 14001, developed by the International Organization for Standardization (ISO) (Prajogo, Tang, & Lai, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several studies have found a positive relationship between environmental management systems (EMSs) and the adoption of eco-innovation in firms, especially in terms of organization and processes [4][5][6][7][8][9]. EMSs can be considered as facilitating and motivational factors for the adoption of eco-innovations in organizations [4,6,[10][11][12][13][14], and over time EMSs have been considered as an initiative to help achieve the goals of sustainable development [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 1.3 billion tons of food waste is produced, which does not only have economic consequences, but it is also harmful to the environment. Generating and disposing waste entails the release of 170 million tons of CO 2 , and 8% of greenhouse gases are generated during disposal . It is an important task to prevent food from becoming waste and to prevent developing food borne diseases, in which developing active packaging that increases shelf life has a major role to play.…”
Section: Introductionmentioning
confidence: 99%
“…Copper has been successfully applied in several food packages, extending the shelf life of food . Most of the literature reports about polymer films that have been activated by copper nanoparticles . There are only a few examples of modified cellulose‐based packaging material …”
Section: Introductionmentioning
confidence: 99%